BEHAVIORAL INTENTION TO USE DIGITAL WALLETS IN INDONESIA - Limanan, Caecelia Cynthia; Keni, Keni (International Journal of Application on Economics and Business, 2023)
The growing number of internet and smartphone users has resulted in the rise of a variety of digital platforms. A digital wallet, which now dominates digital payments, is one type of digital platform. The purpose of this study is to examine the factors that influence behavioral intentions to use a digital wallet in Indonesia using The Unified Theory of Acceptance and Use of Technology (UTAUT). This study examines whether effort expectancy, social influence, and price value significantly affect behavioral intention to use a digital wallet. The number of respondents used is 211 users of one of the digital wallets in Indonesia. All data samples analyzed using the smartPLS 3.2.9 application were declared valid and reliable. PLS-SEM approach will be used to analyze the data in this study. This study concludes that effort expectancy, social influence, and price value have a significant effect on behavioral intentions to use digital wallets. It was also found that the effort expectancy variable is the strongest predictor among exogenous variables that affect endogenous variables.